A population-based study of cognitive impairment in socially vulnerable adults in Argentina: The Matanza Riachuelo Study: Preliminary Results - Bartoloni, Leonardo (2014)
Population aging has taken place intensively worldwide, even in developing countries. These countries have population groups with low resources and basic unmet needs that are frequently omitted from epidemiological studies. OBJECTIVE: The purpose of this study was to determine the prevalence of cognitive impairment (CI) and dementia in an economic and socially vulnerable population from Argentina. METHODS: A door-to-door observational population-based survey among adults over 60 years of cognitive impairment and dementia in the social vulnerable area of the Matanza Riachuelo Basin, in the suburban area of Buenos Aires, Argentina was conducted. Trained psychologists interviewed subjects and a proxy informant. A standardized protocol including a socio-demographic questionnaire, the Mini-Mental State Examination, the Geriatric Depression Scale and a functional inventory for IADL and ADL was administered. Diagnoses were divided into three general categories: normal cognitive function, cognitive impairment-no dementia (CIND) and dementia. RESULTS AND CONCLUSIONS: A total of 2437 elderly persons were assessed, of which 73.6% fulfilled inclusion criteria. The prevalence of CI among those over 60 was 26.4% (18.1% CIND and 8.3% dementia) with higher prevalence of dementia in younger individuals than rates reported in developed counties, probably due to low control of vascular risk factors. This information can help inform health public decisions in the generation of programs and plans for the prevention, diagnosis and treatment of cognitive impairment in this type of socially vulnerable population.